2010
DOI: 10.1007/978-3-642-15705-9_35
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Brachytherapy Seed Reconstruction Using C-Arm Rotation Measurement and Motion Compensation

Abstract: Abstract. During prostate brachytherapy, C-arm flouroscopy images are used for a qualitative assessment of the procedure. Three dimensional reconstruction of the implanted seeds can be used for intraoperative dosimetry and quantitative assessment. Accurate C-arm pose estimation is necessary for 3D localization of the seeds. We propose to measure the C-arm rotation angles and computationally compensate the inevitable C-arm translational motion to estimate the pose. We compensate the oscillation, sagging and whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…For reconstruction of the implant in fluoroscopy, we implemented and used the method described in [7]. The steps for acquiring the fluoroscopy reconstruction included C-arm pose estimation from rotation angle and compensation for sagging, followed by backprojection of the seeds, and finally seed to needle assignment using a minimum cost flow (MCF) algorithm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For reconstruction of the implant in fluoroscopy, we implemented and used the method described in [7]. The steps for acquiring the fluoroscopy reconstruction included C-arm pose estimation from rotation angle and compensation for sagging, followed by backprojection of the seeds, and finally seed to needle assignment using a minimum cost flow (MCF) algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the fluoroscopy reconstruction problem has been extensively addressed. Given 3-5 fluoroscopy images, and the relative pose of the C-arm in each acquisition, the back-projection technique can be used to reconstruct the 3D implant [7]. For registration, attaching fiducial markers to the ultrasound probe [8], using the ultrasound probe itself as a fiducial [4], or using the seeds as fiducials [9] have been mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…The motion compensation algorithm can be combined with other seed matching algorithms, such as REDMAPS (Lee et al, 2011) as reported in Dehghan et al (2010). In comparison to XMARSHAL, REDMAPS provides the optimal matching solution.…”
Section: Tablementioning
confidence: 99%
“…Considering the simplicity of the implementation, high reconstruction accuracy and favorable computational speed, this algorithm is suitable for clinical translation. The underlying idea and limited preliminary data was presented at a recent conference (Dehghan et al, 2010). This manuscript provides a more detailed description of the methodology and performance analysis on 100 clinical data sets.…”
Section: Introductionmentioning
confidence: 99%
“…The latter seed positions are computed from intraoperative fluoroscopic data [6]. We extended the study to include the quantification of seed movement from the intra-operative conditions to immediately after surgery where CT reconstruction is used to compute seed positions [7].…”
Section: Introductionmentioning
confidence: 99%